Efficacy of chronic neck pain self-treatment using press needles: a randomized controlled clinical trial - Horike, Kaori; Ukezono, Masatoshi (Frontiers in Pain Research, 2024)
Background: Chronic neck pain is common among Japanese individuals, but few receive treatment. This randomized controlled trial aimed to evaluate the efficacy of acupuncture using press needles in the self-treatment of chronic neck pain and preliminarily identify the characteristics of patients likely to benefit from this treatment.Methods: Fifty participants with chronic neck pain were allocated to receive either press needle or placebo treatment for 3 weeks. The visual analogue scale (VAS) and motion-related VAS (M-VAS) scores for neck pain, Neck Disability Index score, and pressure pain threshold were measured at baseline, after the first session, at the end of the last session, and 1 week after the last session. Changes in the outcomes were analyzed using analysis of variance, and the relationships between the variables were evaluated using structural equation modeling.Results: Intervention results as assessed by VAS score revealed no significant differences in the ANOVA. A between-groups comparison of M-VAS scores at the end of the last session and baseline showed a significant difference (press needle: -21.64 ± 4.47, placebo: -8.09 ± 3.81, p = 0.025, d = -0.65). Structural equation modeling revealed a significant pain-reducing effect of press needle treatment (β = -0.228, p = 0.049). Severity directly affected efficacy (β = -0.881, p < 0.001). Pain duration, baseline VAS and Neck Disability Index scores were variables explaining severity, while age and occupational computer use were factors affecting severity.Self-treatment with press needles for chronic neck pain did not significantly reduce the VAS score compared to placebo but reduced the motion-related pain as assessed by M-VAS score. A direct association was observed between pain severity and the effectiveness of press needles, and the impact of age and computer were indirectly linked by pain severity.